2021
DOI: 10.1021/acs.chemmater.1c02063
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-Vanadium Binding Enhances Cross-Linking and Mechanics of a Mussel Byssus Coating Protein

Abstract: Inspired largely by chemistry discovered in the byssus fibers of marine mussels, 3,4-dihydroxyphenylalanine (DOPA)−metal coordination has emerged as an effective cross-linking strategy for producing a range of highperformance supramolecular polymers and adhesives with desirable mechanical properties. Recent findings have revealed that mussels often use vanadium in these complexes to enhance the cohesion, rather than solely iron as conventionally believed. Here, we utilized a recombinant DOPA-functionalized mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Not surprisingly, the addition of Fe 3+ to the like-charged mfp-1 coacervates with DTT significantly elevated cohesion (199.4 ± 12.1 mN at pH 5.5 and 289.42 ± 58.62 at pH 7), given the formation of Fe-DOPA complexes and enhanced electrostatic adhesion between positively charged lysine and negatively charged Fe-DOPA complex. Diluted mfp-1 (no coacervate) exhibited high cohesive forces with metals but without thiols in previous SFA experiments. , This SFA result demonstrates that the mfp-1 coacervates exhibit their highest cohesive forces with FeCl 3 under DTT-reducing conditions. In addition, it suggests that the rheology of mfp-1 coacervates can be toggled up or down depending on the oxidation and metal coordination state of DOPA.…”
Section: Results and Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Not surprisingly, the addition of Fe 3+ to the like-charged mfp-1 coacervates with DTT significantly elevated cohesion (199.4 ± 12.1 mN at pH 5.5 and 289.42 ± 58.62 at pH 7), given the formation of Fe-DOPA complexes and enhanced electrostatic adhesion between positively charged lysine and negatively charged Fe-DOPA complex. Diluted mfp-1 (no coacervate) exhibited high cohesive forces with metals but without thiols in previous SFA experiments. , This SFA result demonstrates that the mfp-1 coacervates exhibit their highest cohesive forces with FeCl 3 under DTT-reducing conditions. In addition, it suggests that the rheology of mfp-1 coacervates can be toggled up or down depending on the oxidation and metal coordination state of DOPA.…”
Section: Results and Discussionsupporting
confidence: 50%
“…Diluted mfp-1 (no coacervate) exhibited high cohesive forces with metals but without thiols in previous SFA experiments. 18,50 This SFA result demonstrates that the mfp-1 coacervates exhibit their highest cohesive forces with FeCl 3 under DTT-reducing conditions. In addition, it suggests that the rheology of mfp-1 coacervates can be toggled up or down depending on the oxidation and metal coordination state of DOPA.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…Furthermore, the detection of V in the MSPs is especially noteworthy because it is seldom used in biology in functional roles—especially not as a cross-linking element in materials ( 34 ). It has been recently shown that mussels may preferentially use DOPA-V cross-links to mechanically stabilize the outer protective cuticle of the byssus ( 13 ), and in vitro nanomechanical studies have shown that DOPA-V cross-linking can provide cohesive forces between byssus protein films that are nearly twofold greater than those with DOPA-Fe cross-linking ( 35 ). However, this metal preference has not yet been corroborated in the plaque.…”
mentioning
confidence: 99%
“…Besides Fe 3+ , catechol is also able to coordinate with other metals (e.g., Cu, Zn, Al), and its interaction with vanadium (in the form of V 3+ and VO 2– ) was investigated. At the same ion concentration, the cohesion measured between two recombinant mfp-1 films in the presence of V is much higher than that with Fe, following the trend of V 3+ > VO 2– > Fe 3+ , and the formation of tris-catechol–V complexes could occur at much lower pH values (e.g., pH = 4) . Lee et al detected the interactions of an individual catechol group on a Ti surface by SMFS, and the measured rupture force suggested a dissociation energy of ∼93 kJ/mol, attributed to a strong catechol–Ti coordination .…”
Section: Nanomechanics Of Noncovalent Interactions In Polymeric Systemsmentioning
confidence: 99%
“…At the same ion concentration, the cohesion measured between two recombinant mfp-1 films in the presence of V is much higher than that with Fe, following the trend of V 3+ > VO 2− > Fe 3+ , and the formation of tris-catechol−V complexes could occur at much lower pH values (e.g., pH = 4). 136 Lee et al detected the interactions of an individual catechol group on a Ti surface by SMFS, and the measured rupture force suggested a dissociation energy of ∼93 kJ/mol, attributed to a strong catechol−Ti coordination. 137 This coordination was also demonstrated to be regulated by solution pH.…”
Section: Structure Of Coordination Complexesmentioning
confidence: 99%